Manajemen Budaya Organisasi Bisnis Syariah (Studi di Bank Syariah Indonesia Kantor Cabang Pusat M.H. Thamrin) - Hasbi Ash Shiddieqy; Anike Suci Badriawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Building a business is determined by the parties who set up the business. If a company is founded by people who do not understand religion then the company will tend to be a company that tends to immoral behavior and even at least to wastefulness, as well as companies founded by parties who understand religion will tend to be companies that are more productive and not wasting resources because sharia companies have carried out all the commands of Allah and His Messenger. Because of that, a management concept that is in accordance with sharia is needed in fostering an Islamic Organizational Culture as has been done by PT. Indonesian Sharia Bank. In Islamic management, it must start with a sincere intention because of Allah SWT, performing the five daily prayers, paying zakat, and advising fellow employees. Therefore PT. Bank Syariah Indonesia has implemented Islamic values such as spreading greetings, discipline (punctual), friendly and other commendable qualities. This is because the institutions of the Indonesian Sharia Bank always carry out Islamic studies on a regular basis, namely discussing the Al-Quran and Hadith as guidelines.